Cancer survivorship care and general practice: A qualitative study of roles of general practice team members in Australia. (22nd August 2021) - Fox, Jennifer; Thamm, Carla; Mitchell, Geoff; Emery, Jon; Rhee, Joel; Hart, Nicolas H.; Yates, Patsy; Jefford, Michael; Koczwara, Bogda; Halcomb, Elizabeth; Steinhardt, Raylene; O'Reilly, Roslyn; et al.
Abstract: Primary care providers, including general practice teams (GPTs), are well positioned within the community to integrate cancer survivorship care into ongoing health management. However, roles of GPT members in delivery of cancer survivorship care have not been explored. The purpose of this study is to explore these roles from the perspectives of General Practitioners (GPs), Practice Nurses (PNs) and Practice Managers (PMs). An interpretive qualitative study using semi‐structured in‐depth telephone interviews with ten GPs, nine PNs and five PMs was conducted. Interviews were recorded, transcribed and analysed using grounded theory methods. Perspectives of roles in delivery of cancer survivorship care were highly variable. Variation was evident among perceptions of needs of cancer survivors, individual team members' scopes of practice, and individual professional knowledge and skills. A lack of clarity in roles and responsibilities of GPT members was thought to contribute to a lack of consistency in survivorship care. Reducing variations in perceptions of survivorship care in the primary care setting should be a priority. Such efforts may include development of practical guidance to support GPT members to clarify scopes of practice within the team. In addition to accessible comprehensive education programs, other innovative, tailored individualised education approaches may be helpful. System‐level support in clarifying and supporting the roles of the primary care team is needed to facilitate a survivorship delivery system at general practice level where those within GPT can ensure that individual patients' needs are met in a timely and effective manner.